NGHIÊN CỨU ẢNH HƯỞNG CỦA CÁC YẾU TỐ ĐẾN ĐỘ NHỚT XENLULO BÔNG TINH CHẾ THỦY PHÂN DÙNG ĐỂ ĐIỀU CHẾ NITROXENLULO SỐ 1 VÀ SỐ 2 - Nguyễn, Văn Tính; Nguyễn, Văn Tuân; Nguyễn, Duy Quân (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY ON THE EFFECTS OF SOME FACTORS ON THE HYDROLYTIC PROCESS OF REFINED CELLULOSE COTTON USED TO PREPARE NITROCELLULOSE No.1 AND No.2 The article presents the research results of the effects of some factors on the hydrolytic process of refined cellulose cotton utilized in preparing nitrocellulose No.1 and No.2 for manufacturing single-based propellant. The experimental results indicate that the hydrolysis of refined cellulose cotton in dilute acid solution can reduce the viscosity of the cellulose and the cotton can be used as a raw material to produce nitrocellulose No.1 and No.2 with a high level of uniformity.